1999
DOI: 10.1007/s000180050369
|View full text |Cite
|
Sign up to set email alerts
|

The stress-activated protein kinase pathways

Abstract: Part of the cellular response to toxins, physical stresses and inflammatory cytokines occurs by signalling via the stress-activated protein kinase (SAPK) and p38 reactivating kinase pathways. This results in modification of cellular gene expression. These stress-responsive kinase pathways are structurally similar, but functionally distinct, from the archetypal mitogen-activated protein kinases (MAPKs or ERKs). The ERK pathway is a hierarchical cascade originating at the cell membrane with receptors for mitogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
411
2
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 594 publications
(430 citation statements)
references
References 329 publications
(335 reference statements)
15
411
2
2
Order By: Relevance
“…In agreement with these observations, we found that 5 mM of indirubin-3 0 -monoxime, an amount sufficient to inhibit phosphorylation of the FGFR1OP2-FGFR1 kinase and downstream signaling molecules such as ERK1/2-, PLCg-, STAT1-and STAT3-inhibited proliferation of KG-1a cells. Although indirubin-3 0 -monoxime can activate p38 MAPK, and p38 MAPK has the potential to induce cell death by apoptosis (Tibbles and Woodgett, 1999;Benhar et al, 2001), the growth inhibitory effect of indirubin-3 0 -monoxime on KG-1a cells was not related to activation of p38 MAPK since indirubin-3 0 -monoxime inhibited growth of KG-1a also in the presence of a p38 MAPK inhibitor. Thus, indirubin-3 0 -monoxime has the potential to inhibit growth of FGFR1-dependent cancer cells by directly targeting the FGFR1 tyrosine kinase.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In agreement with these observations, we found that 5 mM of indirubin-3 0 -monoxime, an amount sufficient to inhibit phosphorylation of the FGFR1OP2-FGFR1 kinase and downstream signaling molecules such as ERK1/2-, PLCg-, STAT1-and STAT3-inhibited proliferation of KG-1a cells. Although indirubin-3 0 -monoxime can activate p38 MAPK, and p38 MAPK has the potential to induce cell death by apoptosis (Tibbles and Woodgett, 1999;Benhar et al, 2001), the growth inhibitory effect of indirubin-3 0 -monoxime on KG-1a cells was not related to activation of p38 MAPK since indirubin-3 0 -monoxime inhibited growth of KG-1a also in the presence of a p38 MAPK inhibitor. Thus, indirubin-3 0 -monoxime has the potential to inhibit growth of FGFR1-dependent cancer cells by directly targeting the FGFR1 tyrosine kinase.…”
Section: Discussionmentioning
confidence: 97%
“…Genotoxic drugs like cisplatin (Losa et al, 2003) as well as kinase inhibitors or ultraviolet and g-irradiation (Brancho et al, 2003;Losa et al, 2003) are recognized as agents able to stimulate p38 MAPK as well as JNK pathways (Bulavin et al, 1999;Sanchez-Prieto et al, 2000;Yu et al, 2000). It was reported that stimulation of p38 MAPK and JNK activity is crucial for cisplatin-induced apoptosis (Benhar et al, 2001), but specific inhibition of JNK or p38 MAPK suppresses the drug-induced cell death process (Tibbles and Woodgett, 1999). Our results show that p38 MAPK, but not JNK, is long-term activated in the presence of indirubin-3 0 -monoxime and that activation of FGFR1 is not necessary for the activation of p38 MAPK in our experimental model.…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-activated protein kinases (MAP kinases), also called extracellular signal-regulated protein kinases (ERKs), form a three-level network of proteins that, through successive phosphorylation steps, transduces extracellular signals into cytoplasmic and ultimately nuclear events. 24 The upregulated MAPK pathway in AA rats may thus reflect altered signal transduction upon activation of upstream receptors. Several neurotransmitter receptors, including NMDA, beta-2-adrenergic and CB1 receptors, can induce MAPK and stress-activated protein kinase (SAPK) MAPK cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Target preparation and hybridization were according to the manufacturer's technical manual (Affymetrix, Santa Clara, CA, USA). Briefly, double-stranded cDNA was synthesized using the Superscript Choice System (Gibco BRL, Life Technologies) with an HPLC-purified T7-(dT) 24 primer (Proligo, Boulder, CO, USA), starting with 6 mg of the pooled total RNA. cDNA was then purified with Phase Lock Gel (Eppendorf-5 Prime, Boulder, CO, USA) and phenol/chloroform (Ambion Inc., Austin, TX, USA) extraction, precipitated with ethanol (plus 0.5 ml Pellet Paint), and resuspended in RNase-free water.…”
Section: Affymetrix Oligonucleotide Microarray Hybridizationmentioning
confidence: 99%
“…Fgf13 serves as a cofactor recruiting mitogen-activated protein kinase (MAPK) to the scaffold protein IB2 (Schoorlemmer and Goldfarb, 2001). Extracellular signals including FGFs (Kouhara et al, 1997), neurotropins (Sawada et al, 2000;Patapoutian and Reichardt, 2001), HGF (Stuart et al, 2000) and PDGFs (Lubinus et al, 1994) stimulate several cellular responses involving the activation of MAPK, to coordinate proliferation, differentiation, migration and mitosis (Tibbles and Woodgett, 1999). We now show that Fgf13 expression is detected by WISH within the testis cords of the male genital ridge by at least e13.5 (Fig.…”
Section: Genital Ridge Expression Of Selectedmentioning
confidence: 99%